2022
DOI: 10.1021/acs.jafc.2c04888
|View full text |Cite
|
Sign up to set email alerts
|

Fu Brick Tea Polysaccharides Prevent Obesity via Gut Microbiota-Controlled Promotion of Adipocyte Browning and Thermogenesis

Abstract: The antiobesity efficacy and underlying mechanisms of polysaccharides extracted from Fu brick tea (FBTP) were investigated. An 8-week administration of FBTP dose-dependently inhibited increases in body weight and weights of the epididymal-, retroperitoneal- and inguinal-white adipose tissues and stimulated beige-fat development and brown adipose tissue-derived nonshivering thermogenesis in high-fat diet-induced obese mice. FBTP protected against obesity-associated abnormality in serum adiponectin and leptin, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…It was found that Se-GTP intervention significantly increased the total SCFA content in the colon contents of obese mice, and the contents of acetate, propionate, isobutyrate, butyrate, and valerate were all dramatically elevated. These results indicated that the gut microbiota can utilize Se-GTP to generate SCFAs and subsequently contribute to the treatment of obesity, which is in agreement with the foregoing studies. , Succinate accumulation has been evidenced to control activation of BAT thermogenesis and target adipose browning . The recent study indicated that dietary polysaccharide can be decomposed by the gut microbiota to generate pyruvate, and then, pyruvate will be further converted to succinate .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…It was found that Se-GTP intervention significantly increased the total SCFA content in the colon contents of obese mice, and the contents of acetate, propionate, isobutyrate, butyrate, and valerate were all dramatically elevated. These results indicated that the gut microbiota can utilize Se-GTP to generate SCFAs and subsequently contribute to the treatment of obesity, which is in agreement with the foregoing studies. , Succinate accumulation has been evidenced to control activation of BAT thermogenesis and target adipose browning . The recent study indicated that dietary polysaccharide can be decomposed by the gut microbiota to generate pyruvate, and then, pyruvate will be further converted to succinate .…”
Section: Discussionsupporting
confidence: 86%
“…It is worth concerning that the identified Se-GTP-promoted bacteria such as Lactobacillus, Bif idobacterium, Bacteroides, and Akkermansia have shown great associations with circulating SCFAs in animal studies. 44,45 In order to further probe into the potential mechanism of Se-GTP against obesity and its interrelated metabolic disorders, the metabolites derived from the intestinal flora were analyzed by UPLC-QqQ-MS.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Fu brick tea polysaccharides (FBTP) have been demonstrated to be the main active components in FBT, which primarily consist of arabinose, rhamnose, galactose, mannose and galacturonic acid. 15 Oral FBTP might directly reach the large intestine through the upper digestive tract without being destroyed and exhibit prebiotic-like actions in affecting intestinal microbiota composition. 16 These evidences encouraged us to further investigate whether FBTP could alleviate T2DM by maintaining intestinal homeostasis.…”
Section: Introductionmentioning
confidence: 99%